2013
DOI: 10.1007/s00296-013-2915-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and incidence of systemic lupus erythematosus in South Korea

Abstract: The aim of this study was to estimate the nationwide prevalence and incidence of systemic lupus erythematosus (SLE) in South Korea. National Health Insurance claims data covering almost all Koreans (~50 million) during 2006-2010 were analyzed. Individuals with SLE were identified if (1) they had experienced at least one hospitalization for SLE (International Classification of Diseases, 10th revision code M32), (2) they had taken at least one concomitant prescription of immunosuppressant and hydroxychloroquine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 37 publications
3
28
0
Order By: Relevance
“…Although there was a slight bimodal pattern in incidence by age, the peak age of incidence in this study was between 25-39 years, with a lower incidence rate in the early (20-24 years) and late (40-44 years) childbearing age periods, suggesting that women are at risk of developing SLE during the period of time when they are most likely to have children (25-39 years). These results are consistent with previous Koreans studies that have reported a peak age of incidence in the 30-39 year age ranges [7,21]. The peak age of incidence for SLE in other countries varies: Taiwan and Spain have peak incidence at the age of 20-29, and in Norway, the peak incidence age is 16-29 [11,31,32].…”
Section: Discussionsupporting
confidence: 91%
“…Although there was a slight bimodal pattern in incidence by age, the peak age of incidence in this study was between 25-39 years, with a lower incidence rate in the early (20-24 years) and late (40-44 years) childbearing age periods, suggesting that women are at risk of developing SLE during the period of time when they are most likely to have children (25-39 years). These results are consistent with previous Koreans studies that have reported a peak age of incidence in the 30-39 year age ranges [7,21]. The peak age of incidence for SLE in other countries varies: Taiwan and Spain have peak incidence at the age of 20-29, and in Norway, the peak incidence age is 16-29 [11,31,32].…”
Section: Discussionsupporting
confidence: 91%
“…According to grades of renal biopsy ,in our study ,the distribution of anaemia increase by increasing the grades of renal biopsy but thrombocytopenia was 75% in class (5), 35% in class (4), 50% in class (3) and about 13% in class (2). These results near to the results of (5) which revealed that thrombocytopenia was 80 % in class (5), 32% in class (4), 47 % in class (3) and 12 % in class (2). The study revealed that there was high serum creatinine > 1.3 mg in more than 50% of class (4) and class (5) patients , Although the study of (11) revealed that low percentage of the patients of these classes were affected by high serum creatinine as 34% of class (4) and 41% of class (5) were affected , this may be explained by non compliance of our patients for treatment and by different locality.24 h urinary protein > .5 g affect most of the patients of the studied group , our study as the study (7) as 24 h urinary protein > .5 g affected about 90 % of the patients.…”
Section: Discussionsupporting
confidence: 87%
“…[Epub ahead of print] ics, and Asians, and both the prevalence and incidence of SLE are increasing in the Korean population [3]. In Korea, the prevalence and incidence of SLE between 2006 and 2010 was 20.6 to 26.5 (per 100,000 person) and over 2.5 (per 100,000 person), respectively [4]. SLE is a chronic systemic autoimmune disorder that commonly affects bone homeostasis, which is associated with increased serum levels of various inflammatory cytokines, premature menopause, and maintaining glucocorticoids therapy [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%